Clustering Analysis of Financial Distress on Tourism Sector Companies Go-Public Due to LSSR - Ahmad Firman Maulana; Camelia Iltazami Ulva; Fath Esa Prasanti Kusuma; Faza Budiarti; Moh. Fadli Hidayat DJ Makaraseng; Nyoman Putri Pradievy Syanthi; Rani Nooraeni (Indonesian Journal of Artificial Intelligence and Data Mining, 2021)
Large-Scale Social Restriction Policy (LSSR) to prevent the spread of COVID-19 has a big impact on economic activities, one of which is activities in the tourism sector. Restrictions on outdoor activities reduce the productivity of companies that can lead to bankruptcy. By knowing the financial condition of the company, we can predict whether the company will experience financial pressures or not. This paper tries to analyze the grouping of 100 companies in the tourism sector before (the first quarter of 2020) and after (the second quarter of 2020) the application of LSSR conditions. This paper uses the K-Means grouping method and the financial ratio of each company. Then, the variables in the analysis are Return on Asset (ROA), Total Asset Turn Over Ratio (TATO), Debt to Equity Ratio (DER), and Price to Earning Ratio (PER). The results showed that in the second quarter of 2020 or after the implementation of LSSR, almost all companies tend to be in a financially depressed condition. The number of companies that are under financial pressure after the implementation of this policy is 98 companies.